Yahluma : a sustainable business model? - Metton, Eulalie (SAGE knowledge. Cases., 2016)
In September 2007, Pindiwe Holomisa and Nomaciko Ngoasheng, started Yahluma Solutions Ltd with the intention of building a fully-owned contact centre in Buffalo City (Eastern Cape), and making use of a Department of Trade and Industry (DTI) incentive to encourage the establishment of business process outsourcing and offshoring (BPO&O) businesses. This text analyses Holomisa and Ngoasheng's plans.